Food biotechnology : principles and practice - Joshi, V. K.; Singh,.R. S. (I.K. International, 2012)
This text is primarily aimed at undergraduate and postgraduate students as a reference-cum-textbook. It will be useful both from teaching and research point of view. All chapters have been contributed by experts in their respective fields of research. These will equip readers with the basics and applied research in food biotechnology.